ความสัมพันธ์ระหว่างคุณภาพชีวิตการทำงานกับแรงจูงใจในการทำงาน ของข้าราชการตำรวจในสังกัดโรงเรียนนายร้อยตำรวจ - นุชสำเนียง, ผศ.พันตำรวจโท หญิง ดร.ศิริพร; ชุมวรฐายี, ผศ.พันตำรวจเอก วรวุฒิ (วารสารสหวิทยาการสังคมศาสตร์และการสื่อสาร, 2019)
The objectives of this research were to study the level of quality of work life of the police officers in the royal police cadet academy, to study the relationship between quality of work life and work motivation of them, and to study the quality of work life that could be able to predict work motivation of the policemen. The data were collected using questionnaires from the samples of 231 police officers. The randomly selected with multistage random sampling from all of the police officers working at the royal police cadet academy. In addition, qualitative data were collected using in-depth interviews from eleven police officers. The obtained data were analyzed by using percentage, mean, standard deviation, Pearson’s product moment correlation, and stepwise multiple regression analysis. The results of this study showed that the police officers in the royal police cadet academy had a moderate level of quality of work life (χ = 3.42). The results of in-depth interviews showed that the police officers in the royal police cadet academy had relatively low compensation. But they satisfied with welfare house, public utility, annual health check up, breakfast and lunch welfare. Moreover, the relationship between quality of work life and work motivation of the police officers in the royal police cadet academy was significantly positive at the 0.01 level of significance (r = 0.560**). Finally, the variables could significantly predicted work motivation of the police officers in the royal police cadet academy at the .05 level such as growth and security, social integration, social relevance, and adequate and fair compensation accounted for 64.90 percentage of the variation. (R2 = 0.649)